2005
DOI: 10.2486/indhealth.43.20
|View full text |Cite
|
Sign up to set email alerts
|

Shiftwork: Safety, Sleepiness and Sleep

Abstract: This brief paper reviews the available published literature on shiftwork and safety that allows the relative risk of "accidents" or injuries associated with specific features of shift systems to be estimated. Three main trends in risk are discussed, namely that (i) risk is higher on the night shift, and to a lesser extent the afternoon shift, than on the morning shift, (ii) risk increases over a span of shifts, especially so if they are night shifts, and (iii) risk increases with increasing shift length over e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
133
4
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(151 citation statements)
references
References 8 publications
6
133
4
4
Order By: Relevance
“…The results of the investigation into working hours are in line with some other studies, in which long working hours were shown to be associated with higher health risks and should, therefore, be restricted [11,18]. Regarding type of employment, contractors usually have hard physical work, a lower salary and less job security than formal employees.…”
Section: Discussionsupporting
confidence: 75%
“…The results of the investigation into working hours are in line with some other studies, in which long working hours were shown to be associated with higher health risks and should, therefore, be restricted [11,18]. Regarding type of employment, contractors usually have hard physical work, a lower salary and less job security than formal employees.…”
Section: Discussionsupporting
confidence: 75%
“…In most shift work situations, activities performed may vary in intensity (workload) across the 24-hour work day resulting in a different work environment across shifts (16,25). While we did not have longterm data on workload, we were able to collect information at the time of the officer's visit to the clinic.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Повреде на раду су се најчешће дешавале осам часова након почетка рада (Трнинић-Ђаковић, 2013), а у 12. часу рада ризик од настанка повреда је два пута већи него током првих осам сати рада (Folkard & Tucker, 2003). Показано је и да су 12-часовне смjене биле повезане са 27% повећаним ризиком од незгода, а 10-часовне смjене са 13% ризика (Folkard et al, 2005). Осим тога, значајан број повреда полицајаца настаје и у ситуацијама одступања од редовних смјенских распореда (Vila, 2006).…”
Section: преглед литературеunclassified